Analysis of The Influence of Safety Culture, Safety Leadership, And Safety Knowledge on Safety Performance in Coal Mining Companies in Berau - Raditya Putra Prayoga; Tranggono Tranggono; Mega Cattleya Prameswari Annisa Islami (International Journal of Economics Development Research (IJEDR), 2024)
Occupational safety is crucial for workers in the mining industry, who are involved in tasks such as machine maintenance, heavy equipment mechanics, and welding. These activities carry a high level of risk because coal mining workers operate a lot of heavy machinery, leading to significant risks of workplace accidents or occupational diseases. This final project aims to assess the impact of Safety Culture, Safety Leadership, and Safety Knowledge on Safety Performance to reduce workplace accidents. The research employs Multiple Linear Regression. The data analysis results indicate that Safety Leadership, Safety Knowledge, and Safety Culture all have a significant positive effect on Safety Performance. This means that improvements in Safety Leadership, Safety Knowledge, and Safety Culture correspond to improvements in Safety Performance, thereby reducing workplace accidents.